A bottom-up smart city approach to solid waste management: the case of ICT-enabled waste reclaimers system in two South African cities - Siwawa, Vincent (University of the Witwatersrand, Johannesburg, 2023)
This study delves into the realm of waste management in the context of bottom-up smart cities, focusing on the implementation of an innovative ICT-enabled waste reclaimer system in Cape Town and Johannesburg, South Africa. The central inquiry pertains to the pivotal role played by the bottom-up smart city paradigm in addressing waste management challenges and fostering the inclusion of waste reclaimers within the framework of smart cities. The inadequacies inherent in prevailing top-down smart city approaches and techno-centric solutions extends to the lack of mechanisms within the conventional informal recycling system to furnish reliable, immutable, and transparent waste-related data, thereby compromising security. To address these challenges, a novel approach emerges, fusing the capabilities of the Internet of Things (IoT) and blockchain technology into the informal recycling sector. This ICT-enabled waste reclaimer system introduces a comprehensive framework encompassing training initiatives, the provisioning of protective equipment, smartphones to facilitate communication between households and waste reclaimers, measuring instruments, tricycles, and dedicated spaces for sorting and storing recyclable materials. Employing a qualitative research methodology, this study incorporates a blend of document analysis, integrative literature review, and semi-structured interviews with key stakeholders. The selection of case studies, namely BanQu, Kudoti, and Regenize, is underpinned by purposive sampling. An array of research instruments including webinars, photography, participant observations, and transect walks contribute to the rich data collection process. The study draws upon the socio-technical transition theory to sustainability and the Multi-Level Perspective (MLP) as conceptual frameworks to dissect the digital transformation of the informal waste sector through the lens of the ICT-enabled waste reclaimer system. Findings underscore the potential of this innovative system to foster symbiotic connections between waste reclaimers and stakeholders embedded within the recycling value chain. This, in turn, culminates in enhanced working conditions and augmented income for waste reclaimers. Crucially, the ICT-enabled waste reclaimer system offers mechanisms for waste monitoring and tracking, while concurrently introducing incentives and rewards. By generating precise, secure, and reliable data, this system engenders a paradigm shift from a conventional cash- based payment structure to a virtual and electronic payment mechanism. Preliminary evidence showcases a notable threefold increase in recyclable collection by waste reclaimers compared to municipal efforts. In culmination, this study delivers both theoretical and empirical contributions by shedding light on the integration of waste reclaimers and waste management within the context of a bottom-up smart city approach. The study posits a promising trajectory for future research and ushers in new avenues for the development of bottom-up smart cities within the ambit of developing nations.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy in Civil Engineering, In the Faculty of Engineering and the Built Environment, School of Civil & Environmental Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Smart city; bottom-up approach; internet of things; blockchain technology; ICT-enabled waste reclaimers' system; integration; municipal solid waste management; circular economy; zero waste goal; SDG-11: Sustainable cities and communities; SDG-9: Industry, innovation and infrastructure